2015
DOI: 10.1016/j.molmet.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Activation of natriuretic peptides and the sympathetic nervous system following Roux-en-Y gastric bypass is associated with gonadal adipose tissues browning

Abstract: ObjectiveRoux-en-Y gastric bypass (RYGB) is an effective method of weight loss and remediation of type-2 diabetes; however, the mechanisms leading to these improvements are unclear. Additionally, adipocytes within white adipose tissue (WAT) depots can manifest characteristics of brown adipocytes. These ‘BRITE/beige’ adipocytes express uncoupling protein 1 (UCP1) and are associated with improvements in glucose homeostasis and protection from obesity. Interestingly, atrial and B-type natriuretic peptides (NPs) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 49 publications
4
47
0
1
Order By: Relevance
“…We note that a common feature between the cold exposure and endurance exercise is the negative energy balance: higher energy expenditure than intake leading to fat loss. In addition, interventional microbiota depletion, either by means of antibiotics administration or in germ-free mice (Suá rez-Zamorano et al, 2015;Chevalier et al, 2015), as well as RYGB (Neinast et al, 2015) also increase the browning to a similar extent as several endurance exercise regimens. These are also conditions of decreased caloric uptake and negative energy balance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We note that a common feature between the cold exposure and endurance exercise is the negative energy balance: higher energy expenditure than intake leading to fat loss. In addition, interventional microbiota depletion, either by means of antibiotics administration or in germ-free mice (Suá rez-Zamorano et al, 2015;Chevalier et al, 2015), as well as RYGB (Neinast et al, 2015) also increase the browning to a similar extent as several endurance exercise regimens. These are also conditions of decreased caloric uptake and negative energy balance.…”
Section: Discussionmentioning
confidence: 96%
“…Browning appears consequent to physiological stimuli, such as cold exposure or endurance exercise (Cousin et al, 1992;Guerra et al, 1998;Himms-Hagen et al, 2000). In addition to the physiological stimuli, also microbiota depletion (Suá rez-Zamorano et al, 2015;Chevalier et al, 2015) and Roux-en-Y gastric bypass weight-loss surgery (RYGB) (Neinast et al, 2015) promote the development of beige fat. It remains unclear whether there is a common feature between these seemingly unrelated physiological and interventional stimuli that could lead to the beige fat development.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that the reduced ADRB3 expression in adipose tissue of obese rats [9, 10] increased after weight loss following Roux-en-Y gastric bypass surgery [25]. Moreover, treatment with ADRB3 agonists caused a noticeable increase of adipose tissue browning and UCP-1 protein level in lean rather than in obese mice [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…A great number of pharmacological and physiological stimuli can trigger beige adipocyte accumulation in rodents and humans beyond cold exposure, including cancer cachexia, gastric bypass, exercise, and burn trauma (Kir et al 2014;Neinast et al 2015;Sidossis et al 2015;Stanford et al 2015). Great progress has been made in elucidating the transcriptional machinery and signaling cascades driving brown and beige adipocyte accumulation; however, in most cases, the actual cellular origin of the UCP1 + adipocytes accumulating under physiological conditions or in genetic models has remained unclear.…”
Section: Recruitment Of Beige Adipocytes In Adultsmentioning
confidence: 99%